PENGARUH PAJAK DAN RETRIBUSI TERHADAP PENDAPATAN ASLI DAERAH (PAD) KOTA MAGELANG TAHUN 2011-2023 - Kumalasari, Reta; Samudra, Gilang (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2025)
Local Own-source Revenue (PAD) is an important indicator for assessing the independence of a region. Taxes and retribution have a strategic role as contributors to Local Own-source Revenue (PAD). The growth of Local Own-source Revenue (PAD), taxes and retribution in Magelang City over the last 13 years shows significant variations/fluctuations. This indicates instability in the management of regional income sources. This research aims to analyze the influence of regional taxes and local retribution on Original Regional Income in Magelang City for the 2011-2023 period. The data used is time series data from 2011 to 2023 on an annual basis obtained from the Directorate General of Financial Balance of the Ministry of Finance (https://djpk.kemenkeu.go.id/). The research method uses multiple linear regression analysis. The research results show that taxes have a positive and very significant influence on Original Regional Income in Magelang City amounting to 7.218, while local retribution have a negative and significant influence on Original Regional Income in Magelang City amounting to -23.922. Together, taxes and levies have a significant effect on Local Own-source Revenue in Magelang City for the 2011-2023 period. Optimizing local taxes and levy policy reform must prioritize efficiency (low management costs) and effectiveness (maximum revenue with direct benefits for society). If carried out consistently, then these steps can significantly increase Local Own-source Revenue, strengthen the regional economy, and improve the welfare of the people of Magelang City.